2021
DOI: 10.3389/fmed.2021.663670
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and the Long-Term Post-recovery Manifestations of the COVID-19 Patients—A Prospective Multicenter Cross-Sectional Study

Abstract: Objective: Coronavirus disease 2019 (COVID-19) or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a global issue. In addition to managing acute cases, post-COVID-19 persisting symptoms/complaints and different hematological values are of great concern. These have an impact on the patient's well-being and are yet to be evaluated. Therefore, clinical and primary diagnosis based on routine laboratory findings bears high importance during the initial period of COVID-19, especially in regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 29 publications
3
35
1
3
Order By: Relevance
“…The lowest prevalence was reported by Mohiuddin Chowdhury et al, for both mild body ache and back pain (0.3%) persisting for 4 weeks following recovery. 25 The highest prevalence of 65.2% COVID-19 survivors reporting new-onset pain at 16 weeks after hospital discharge has been reported by Carvalho-Soares et al 26 …”
Section: Synthesis Of Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The lowest prevalence was reported by Mohiuddin Chowdhury et al, for both mild body ache and back pain (0.3%) persisting for 4 weeks following recovery. 25 The highest prevalence of 65.2% COVID-19 survivors reporting new-onset pain at 16 weeks after hospital discharge has been reported by Carvalho-Soares et al 26 …”
Section: Synthesis Of Resultsmentioning
confidence: 95%
“… Both depression and neuropathic pain may arise from a common underlying inflammatory process induced by the cytokine storm. Mahmud et al (2021) 96 Bangladesh 355 (207/148) N=162 with post-covid syndrome (symptomatic) N=193 no post-covid symptoms Yes Prospective cohort study 4 weeks after clinical improvement Myalgia Total (0.6%) Symptomatic (1.2%) Arthralgia Total (1.4%) Symptomatic (4.8%) Chest pain Total (0.8%) Symptomatic (1.8%) Not available Not available Not available Mohiuddin Chowdhury et al (2021) 25 Bangladesh 313 (251/62) Yes (n=62) No (n=251) Prospective multicenter cross-sectional study 4 weeks following recovery. Arthralgia (0.6%) Mild body ache (0.3%) Back pain (0.3%) Not available Not available Not available Moradian et al (2020) 97 Iran 200 (160/40) Yes Cross-sectional study 6 weeks after discharge Myalgia 8% Not available Not available Not available Moreno-Perez et al (2021) 98 Spain 277 (146/131) Severe (hospitalized) Mild (hospital follow-up) Prospective covid study 8–12 weeks Myalgias-arthralgias 19.6% Not available Not available Not available Ong et al (2021) 66 Singapore 288 (243/45) Yes …”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Epidemiologists surveyed the patient groups and found that most patients developed at least one long-term symptom [ 6 , 9 ]. Women were more likely to develop long COVID than men; elderly people were more likely to develop long COVID than young people [ 57 ]; and existing comorbidity and BMI index were also associated with long COVID [ 58 , 59 ]. Children are a special group.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Parker et al. concluded that higher values of CRP were measured in patients diagnosed with all three infections: TB, HIV, and COVID-19 ( 67 ). However, researchers recommend CRP as a monitoring and prognosis tool in patients diagnosed with both TB and COVID-19, rather than as a rule-out screening test ( 68 ).…”
Section: Discussionmentioning
confidence: 99%